Topographic waves in barotropic flow - KUMARJAIN, ANIL (MAUSAM, 1989)
Technique, of Fourier series analysis is used to study linear and non-Linear effects on the instability of a basic state consisting of a topographically force wave in an inviscid barotropic beta plane model. It is shown that an analytical study on instability is possible It amplitude of wave like perturbation is either an even or odd function In space about origin. The study is carried out in the present paper for former case.